THE VULNERABILITY OF DIFFERENT POPULATIONS OF THE COMMERCIALLY-IMPORTANT SHRIMP PANDALUS BOREALIS TO ENVIRONMENTAL STRESS ... - Hall, Emilie Florence (University of Plymouth, 2017)
The present study adopted an integrative approach to conduct a population comparison of vulnerability to environmental stress in a commercially important species of ectotherm. Specifically, I investigated how differing environmental conditions in native habitats may drive intra-species divergence and alter performance when conditions shift. This study used northern prawn (Pandalus borealis Krøyer 1838) populations with known morphological differences from two spatially proximate fjord sites differing in oxygen regime as a model system. The genetic population structure was analysed and whole organism, physiological, and metabolomic performance under hypoxia and thermal stress were assessed. Genetic analyses displayed no significant dissimilarities between P. borealis from the normoxic and the seasonally hypoxic site. It was hypothesised that phenotypic plasticity may act as mechanism by which P. borealis may persist in the seasonally hypoxic fjord. Subsequently, a common garden experiment, in which ...